Mapping Global Internal Control Research: A Bibliometric Analysis of Publication Trends, Emerging Themes, and Collaboration Patterns in Scopus (2022–2025) - Dodi Dahyawan; Fitriana Dachlan; Rachmat Agus Santoso (Manunggal Halim Jaya, 2026)
Internal control has become increasingly important as organizations integrate governance, enterprise risk management, and digital transformation into organizational decision making. The COSO Integrated Framework establishes internal control as the foundation of governance and risk management, while digital transformation has fundamentally reshaped organizational processes and control systems (COSO, 2013 ; Vial, 2019). This study maps the global development of internal control research using a bibliometric approach based on Scopus-indexed publications from 2022 to 2025. Data were analyzed using Biblioshiny after a systematic screening process that resulted in 934 eligible articles in the Business, Management and Accounting subject area. The analysis examined publication growth, influential authors, source journals, country collaboration, citation performance, and keyword evolution. The findings reveal a substantial increase in global research productivity during the study period, accompanied by stronger international collaboration and the emergence of new thematic areas. China emerged as the leading contributor to global internal control research, while corporate governance, digital transformation, risk management, audit quality, environmental, social and governance (ESG), and artificial intelligence emerged as the dominant research themes. The bibliometric evidence further demonstrates a clear shift from conventional internal control systems toward digitally enabled governance and intelligent control mechanisms. This study contributes by providing a comprehensive knowledge map of recent internal control research, identifying emerging research directions, and offering practical references for researchers interested in governance, auditing, and organizational control systems.